2014
DOI: 10.1016/j.stemcr.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Ex Vivo Expansion of Fully Functional Salivary Gland Stem Cells

Abstract: SummaryHyposalivation often leads to irreversible and untreatable xerostomia. Salivary gland (SG) stem cell therapy is an attractive putative option to salvage these patients but is impeded by the limited availability of adult human tissue. Here, using murine SG cells, we demonstrate single-cell self-renewal, differentiation, enrichment of SG stem cells, and robust in vitro expansion. Dependent on stem cell marker expression, SG sphere-derived single cells could be differentiated in vitro into distinct lobular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
183
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(195 citation statements)
references
References 25 publications
(31 reference statements)
7
183
2
1
Order By: Relevance
“…The original short-term culture technology depended on FGF, EGF, and Matrigel. The cultured cells were able to efficiently restore radiation-damaged salivary gland function in transplanted mice (Nanduri et al, 2014). In a follow-up study, robust Wnt pathway activation through the addition of Wnt3A and R-spondin allowed long-term expansion of the organoids, containing all differentiated salivary gland cell types.…”
Section: Salivary Glandmentioning
confidence: 96%
“…The original short-term culture technology depended on FGF, EGF, and Matrigel. The cultured cells were able to efficiently restore radiation-damaged salivary gland function in transplanted mice (Nanduri et al, 2014). In a follow-up study, robust Wnt pathway activation through the addition of Wnt3A and R-spondin allowed long-term expansion of the organoids, containing all differentiated salivary gland cell types.…”
Section: Salivary Glandmentioning
confidence: 96%
“…Sorted cells were embedded in Basement Membrane Matrigel (BD Biosciences) and seeded in 12-well. Cells were cultured in expansion medium (EM) as previously published [6] (DMEM:F12 containing Pen/Strep antibiotics (1Â; Invitrogen), Glutamax (1Â; Invitrogen), N2 (1Â; Gibco), EGF (20 ng/ml; SigmaAldrich), FGF2 (20 ng/ml; Sigma-Aldrich), insulin (10 lg/ml; Sigma-Aldrich), dexamethasone (1 lM; Sigma-Aldrich), Y-27632 (10 lM; Sigma-Aldrich)).…”
Section: Micementioning
confidence: 99%
“…In a preclinical model, we [2,3] and others [4] have previously shown that stem/progenitor cell transplantation not only rescues hyposalivation, but also restores tissue homeostasis of the irradiated gland, necessary for long-term maintenance of adult tissue [5]. Additionally, we demonstrated optimized culturing conditions for long-term in vitro expansion of CD24 hi /CD29 hi salivary gland stem cells (SGSCs) [6]. Moreover, similar results have been found with human salivary gland derived cells [7,8].…”
mentioning
confidence: 93%
“…hi (Nanduri et al 2014)-have all been implicated as salivary gland stem or progenitor cells. , and duct).…”
Section: Evidence For Salivary Gland Stem and Progenitor Cellsmentioning
confidence: 99%
“…Recent data based on a histone H2BGFP model characterized mitotically active cells in the ID and excretory duct (Kwak and Ghazizadeh 2014), sites of cKit-expressing cell populations thought to represent stem cells (Pringle et al 2013). Although many of these cell populations display stem or progenitor cell potential in vitro (Hisatomi et al 2004;Matsumoto et al 2007;Sato et al 2007;David et al 2008;Lombaert et al 2008) and some demonstrate regenerative properties when transplanted into irradiated glands (Lombaert et al 2008;Nanduri et al 2014), their in vivo differentiation potential must still be established.…”
Section: Evidence For Salivary Gland Stem and Progenitor Cellsmentioning
confidence: 99%